Caracterização mineralógica de itabiritos da Serra do Sapo, MG: aplicação da técnica Mineral Liberation Analyser - MLA - Amanda de Almeida Pires e Souza (2014)
This work presents mineralogical characterization of the itabirites of Serra do Sapo deposit. The deposit is 15 km long and located in the eastern portion of the southern Espinhaço Range, near the city of Conceição do Mato Dentro, Minas Gerais, Brazil. Supergene low to medium- grade iron ore (31 to 39%) are classified in itabirite, semi-friable and friable or soft itabirite, with variable grade according to the degree of weathering and compactness, mainly composed of hematite and quartz. Hematite crystals were classified after their textural and morphological characteristics as: microplaty, anhedral, platy, and martite (pseudomorphic after magnetite). Geochemical analysis show that the three types of itabirites are similar regarding the content of CaO (0,14 wt%), MgO (0,04 wt%), MnO (0,21 wt%), Al2O3(0,94 wt%), K2O (0,27 wt%), TiO2 (0,05 wt%) e P2O5 (0,11 wt%), with major grades of Al2O3, MgO and K2O present in semifriable and friable itabirites, and of CaO and P2O5 in hard itabirite. The autigenic U, V/Cr and Ni/Co indexes point to an oxic environment of sedimentation. Ratios of (Eu/Sm)SN, (La/Sm)CN, (Sm/Yb)SN, (Eu/Eu*)SN, and (Sm/Yb)CN indicate that the banded iron formation represented by itabirite is free of clastic contamination, and the ratios of Sm/Yb vs. Eu/Sm and of Eu/Eu*(CN) vs. (Sm/Yb)(CN) indicate insignificant contribution of high temperature hydrothermal fluids. The mineralogical characterization using the Mineral Liberation Analyser software indicated, as well as microscopic petrography, that all types of itabirites show similar mineralogical association. The textural characteristics of the particles show a complex interlocking of gangue minerals with iron oxide mainly in the coarser grain sizes. The concentration of Fe is higher in the friable itabirite than other types, as well as the concentrations of Al, K, Mg and F. The concentrations of Ca, P and Ba are higher in itabirite. Particles of iron oxide are free in the greater proportion friable itabirite and lower concentrations of Fe are in the particle size range 105+74 m. In all itabirites the mixed particles are generally associated with the quartz and mica to a lesser extent. Associantios with apatite and carbonate can still occur, in hard and friable itabirite, respectively. Friable itabirite shows liberation degrees of iron oxide in both free surface and by the composition of the particle much larger than the hard itabirite. It is also observed that the recovery of iron content as iron oxide in friable itabirite is much higher than the itabirite and semi-friable itabirite. Thus, during the stages of ore processing, friable itabirite must submit a better use, followed by semi-compact itabirite and the itabirite that must undergo further processing steps to improve their productivity.